The wettability enhancement of SiC particles in cast aluminum a356 matrix composites - Ghandvar, Hamidreza (2013)
A study has been conducted using compocasting technique to investigate the wettability enhancement of SiC in aluminum matrix composite. Aluminum matrix composite reinforced with SiC is produced by the addition of 1% Mg powder which have impact on a uniform distribution of SiC in the Aluminum matrix. In addition, it is worthwhile to mention that there is mutual relationship between a uniform distribution of SiC in the aluminum matrix and mechanical properties. The findings show that there are some important determinants, which have strong influence on a uniform distribution of SiC in the Aluminum matrix such as surface treatment of SiC, addition of alloy elements including Mg and other elements, particle size, percentage of Mg, stirring speed and stirring method and solidification rate. Among of mentioned determinants, the results show that addition of Mg into melt is the salient predictor. In addition, there is a direct relationship between mechanical properties and a uniform distribution of silicon carbide inside the aluminum matrix. Result from the mechanical testings and the microstructural show that the addition of 1% Mg improves the wettability of the aluminum/SiC composites.